COVID-19 vaccination-related tinnitus is associated with pre-vaccination metabolic disorders - Wang, Weihua; Yellamsetty, Anusha; Edmonds, Robert M.; Barcavage, Shaun R.; Bao, Shaowen (Frontiers in Pharmacology, 2024)
Cases of tinnitus have been reported following administration of COVID-19 vaccines. The aim of this study was to characterize COVID-19 vaccination-related tinnitus to assess whether there is a causal relationship, and to examine potential risk factors for COVID-19 vaccination-related tinnitus. We analyzed a survey on 398 cases of COVID-19 vaccination-related tinnitus, and 699,839 COVID-19 vaccine-related reports in the Vaccine Adverse Effect Reporting System (VAERS) database that was retrieved on 4 December 2021. We found that following COVID-19 vaccination, 1) tinnitus report frequencies for Pfizer, Moderna and Janssen vaccines in VAERS are 47, 51 and 70 cases per million full vaccination; 2) the symptom onset was often rapid; 3) more women than men reported tinnitus and the sex difference increased with age; 4) for 2-dose vaccines, the frequency of tinnitus was higher following the first dose than the second dose; 5) for 2-dose vaccines, the chance of worsening tinnitus symptoms after second dose was approximately 50%; 6) tinnitus was correlated with other neurological and psychiatric symptoms; 7) pre-existing metabolic syndromes were correlated with the severity of the reported tinnitus. These findings suggest that COVID-19 vaccination increases the risk of tinnitus, and metabolic disorders is a risk factor for COVID-19 vaccination-related tinnitus.